The Importance of Photography as an Information Support in Event Management (Case Event of Anugerah Bambu Indonesia 2013) - Anwar Basalamah; Maria Pia Adiati (Bina Nusantara University, 2013)
This study aims to investigate the potential of media photography as a means of support in an event practice, analyze photography as data source in identifying the event practice, explore photography as documentation that helps in event execution, examine photography as visual language that supports the event management. From the case of an event organized by Anugerah Bambu Indonesia 2013, results from the study finds that photography has an added value as a data source, documentation, and visual language. This study proves that the theory EMBOK by Silvers, who categorizes photography as information management for event management, a theory which can be accounted for.